ICT SOLUTION TO MINIMIZE ILLEGAL, UNREPORTED AND UNREGULATED (IUU) FISHING - Nisansala, Aruni; Kodikara, Nihal; Keppitiyagama, Chamath; Sandaruwan, Damitha; Dias, Kapila; Senadheera, Ranjith; Weerasinghe, Maheshya; Buddika, Ishan; Lakshika, Chamal; Dammika, Nuwan; Liyanage, Nadun; Nirmal, Isura (International Journal of Research -GRANTHAALAYAH, 2015)
Marine environment is one of the natural ecosystem which is been affected by the unscrupulous human activities. Lots of efforts are taken to preserve and maintain the balance of the aquatic resources by responsible bodies. European Union convention on the law of the sea has a great impact on avoiding the IUU fishing activities of the countries with large scaled fisheries industry. Fishing grounds should be harvested with caution otherwise whole could be endanger in extinction while harvesting the whole school of fish. There the fishermen are responsible for releasing under-weight fishes and the other fish types which are prohibited to be caught. With the technology all the manual works has been eased and heightened in accuracy wise. Albeit the advantages are there, the main drawback is that they are being expensive. Localizing those products and requirement adding has been the major gap which has limited those commercial products being popularized in the countries with native languages. In this paper we have discussed a novel approach for fishing vessel tracking and catch reporting which minimizes above drawbacks.